The Effect of Dark Chocolate on Dysmenorrhea in Young Women at Stikes Raflesia Depok - Qoriyah, Rika; Wulandari, Priharyanti (Indonesian Journal of Global Health Research, 2023)
Dysmenorrhea can affect young women's learning activities. Treatment of dysmenorrhea can be overcome with non-pharmacological therapy, such as dark chocolate. The magnesium content in dark chocolate can block prostaglandin hormones that trigger uterine muscle tension. The purpose of this study was to determine the effect of dark chocolate on dysmenorrhea in adolescent girls. This type of research is a quantitative method with a pre-experiment design of one group pretest-posttest without a control group. The subjects of this study were adolescent girls with primary dysmenorrhea on the first and second days, with as many as 55 respondents. The sample consisted of 30 respondents with a stratified random sampling technique. The data collection technique uses a numeric rating scale and a Wilcoxon data analysis test. In the univariate analysis of the degree of dysmenorrhea before and after the first and second days of dark chocolate, the highest category was medium, and after dark chocolate, the highest category was mild. The results of the Wilcoxon test on the first and second days showed the effect of dark chocolate on dysmenorrhea in young women with a p-value of 0.000 (p < 0.05). There was a decrease in the degree of dysmenorrhea after giving dark chocolate 100 grams (72%) to young women at STIKes Raflesia Depok.